Supply chain excellence a handbook for dramatic improvement using the SCOR model - Bolstorff, Peter (American Management Association, 2012)
"To keep your sales, manufacturing, distribution, and inventory moving in perfect synchronization, you need a flawless, repeatable supply chain improvement approach that maximizes process efficiency, eliminates dysfunction, and aligns disparate organizationsùglobally. Supply Chain Excellence, ahead of the curve in its original edition, again breaks new ground with a highly compressed timeline for using the SCOR (Supply Chain Operations Reference) framework to plan and execute supply chain improvement. In addition to the value chain processes of DCOR and CCOR, the book is now adapted for use in an SAP environment, in global enterprises, and by small businesses. Featuring examples and experience from roughly 100 projects, the completely updated third edition refines the use of the scorecard for better process analysis; extends the approach to encompass implementation and strategy; and quantifies the financial value of supply chain improvement to demonstrate its importance in achieving lasting competitive advantage."--